Transparent Conductive Zinc Oxide Basics and Applications in Thin Film Solar Cells - Ellmer, Klaus; Klein, Andreas; Rech, Bernd; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2008)
Zinc oxide (ZnO) belongs to the class of transparent conducting oxides which can be used as transparent electrodes in electronic devices or heated windows. In this book the material properties of, the deposition technologies for, and applications of zinc oxide in thin film solar cells are described in a comprehensive manner. Structural, morphological, optical and electronic properties of ZnO are treated in this review. The editors and authors of this book are specialists in deposition, analysis and fabrication of thin-film solar cells and especially of ZnO. This book is intended as an overview and a data collection for students, engineers and scientist.
ZnO and Its Applications -- Electrical Properties -- Optical Properties of ZnO and Related Compounds -- Surfaces and Interfaces of Sputter-Deposited ZnO Films -- Magnetron Sputtering of ZnO Films -- Zinc Oxide Grown by CVD Process as Transparent Contact for Thin Film Solar Cell Applications -- Pulsed Laser Deposition of ZnO-Based Thin Films -- Texture Etched ZnO:Al for Silicon Thin Film Solar Cells -- Chalcopyrite Solar Cells and Modules.
Keywords: Physics; Solid state physics; Optics; Optoelectronics; Plasmons (Physics).; Spectroscopy; Microscopy; Optical materials; Electronic materials; Physics; Optics, Optoelectronics, Plasmonics and Optical Devices; Solid State Physics; Spectroscopy and Microscopy; Optical and Electronic Materials; Electronic books